Functional Requirement for Orai1 in Store-operated TRPC1-STIM1 Channels - Cheng, Kwong Tai (American Society for Biochemistry and Molecular Biology, 2008)
Orai1 and TRPC1 have been proposed as core components of store-operated calcium release-activated calcium (CRAC) and store-operated calcium (SOC) channels, respectively. STIM1, a Ca(2+) sensor protein in the endoplasmic reticulum, interacts with and mediates store-dependent regulation of both channels. We have previously reported that dynamic association of Orai1, TRPC1, and STIM1 is involved in activation of store-operated Ca(2+) entry (SOCE) in salivary gland cells. In this study, we have assessed the molecular basis of TRPC1-SOC channels in HEK293 cells. We report that TRPC1+STIM1-dependent SOCE requires functional Orai1. Thapsigargin stimulation of cells expressing Orai1+STIM1 increased Ca(2+) entry and activated typical I(CRAC) current. STIM1 alone did not affect SOCE, whereas expression of Orai1 induced a decrease. Expression of TRPC1 induced a small increase in SOCE, which was greatly enhanced by co-expression of STIM1. Thapsigargin stimulation of cells expressing TRPC1+STIM1 activated a non-selective cation current, I(SOC), that was blocked by 1 μm Gd(3+) and 2-APB. Knockdown of Orai1 decreased endogenous SOCE as well as SOCE with TRPC1 alone. siOrai1 also significantly reduced SOCE and I(SOC) in cells expressing TRPC1+STIM1. Expression of R91WOrai1 or E106QOrai1 induced similar attenuation of TRPC1+STIM1-dependent SOCE and I(SOC), whereas expression of Orai1 with TRPC1+STIM1 resulted in SOCE that was larger than that with Orai1+STIM1 or TRPC1+STIM1 but not additive. Additionally, Orai1, E106QOrai1, and R91WOrai1 co-immunoprecipitated with similar levels of TRPC1 and STIM1 from HEK293 cells, and endogenous TRPC1, STIM1, and Orai1 were co-immunoprecipitated from salivary glands. Together, these data demonstrate a functional requirement for Orai1 in TRPC1+STIM1-dependent SOCE.